x+(x+1)=x-1

Simple and best practice solution for x+(x+1)=x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+(x+1)=x-1 equation:


Simplifying
x + (x + 1) = x + -1

Reorder the terms:
x + (1 + x) = x + -1

Remove parenthesis around (1 + x)
x + 1 + x = x + -1

Reorder the terms:
1 + x + x = x + -1

Combine like terms: x + x = 2x
1 + 2x = x + -1

Reorder the terms:
1 + 2x = -1 + x

Solving
1 + 2x = -1 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
1 + 2x + -1x = -1 + x + -1x

Combine like terms: 2x + -1x = 1x
1 + 1x = -1 + x + -1x

Combine like terms: x + -1x = 0
1 + 1x = -1 + 0
1 + 1x = -1

Add '-1' to each side of the equation.
1 + -1 + 1x = -1 + -1

Combine like terms: 1 + -1 = 0
0 + 1x = -1 + -1
1x = -1 + -1

Combine like terms: -1 + -1 = -2
1x = -2

Divide each side by '1'.
x = -2

Simplifying
x = -2

See similar equations:

| y3/2-1 | | 8x-9=2+5x | | 7x-9=21+5x | | 12e-(19)=7-e | | (9x-3)=(3x+6) | | 6cos(x)+8sin(x)=5 | | y(y-6)=16 | | 5x^2-9=12x | | 7/5x=49 | | 3(6y+7)+7y= | | f(x)=(x-3)(2x+6) | | Ax-3x=5forx | | 8y-(3+4y)= | | m=4Gz | | 4x^2+7=-11x | | Ac-3x=5 | | 9/10()=18 | | 8v^2=56v | | Ax-3x=c | | 7g-15=41 | | x^3+3x^2-6x+12=0 | | 144-3x=180 | | x^3-3x^2-6x+12=0 | | 9x^2-12x+62=0 | | x*11+11=x*5+83 | | 8r^2+4r-6=0 | | 2(u-9)-4=-2(-9u+6)-u | | 2(4u+9)=14 | | x+2x=11x | | 12d+3=6d+45 | | 3x^2+16x-35=o | | 4(x-2)=6.4 |

Equations solver categories